2022
DOI: 10.3390/en15207511
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Deformation Characteristics and Energy Analysis of Mudstone under Water Absorption Process

Abstract: In geological engineering, a series of safety problems caused by expansive mudstone are common, such as slope instability and roadbed up-arch. In this paper, the mineral composition of mudstones in the Xining area was analyzed by X-ray diffraction (XRD), and the microstructural and morphological changes of mudstones after water absorption were observed by scanning electron microscopy (SEM) test to analyze the internal factors and microstructural evolution patterns of water absorption and swelling of mudstones.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the distribution of voids plays a crucial role in influencing the tensile strength and crack mode of the material. Feng et al [23] observed the microstructure and morphological changes of mudstone after water immersion. The results indicated that the nonhomogeneous strain of mudstone led to the expansion between adjacent clay mineral aggregates and particle clusters, resulting in the reduction in or disappearance of pores, which causes a decrease in the number of large-diameter pores and an increase in the number of small-diameter pores in the internal pores of mudstone.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the distribution of voids plays a crucial role in influencing the tensile strength and crack mode of the material. Feng et al [23] observed the microstructure and morphological changes of mudstone after water immersion. The results indicated that the nonhomogeneous strain of mudstone led to the expansion between adjacent clay mineral aggregates and particle clusters, resulting in the reduction in or disappearance of pores, which causes a decrease in the number of large-diameter pores and an increase in the number of small-diameter pores in the internal pores of mudstone.…”
Section: Introductionmentioning
confidence: 99%
“…Water rock interaction exists widely in various practical geotechnical engineering. Under the action of water, the rock will often be softened, cracked, expanded, disintegrated and other deterioration phenomena (Zhao et al, 2021;Zhou K. et al, 2022;Feng et al, 2022;, and this deterioration of rock in water has a great impact on the safety of various engineering construction (Bai et al, 2021;Du et al, 2022;Fu et al, 2022). Therefore, the research on the law of rock wetting deterioration has always been the focus of researchers (Jiang et al, 2015;Hua et al, 2019).…”
Section: Introductionmentioning
confidence: 99%